Influence of the flow profile to Lorentz force velocimetry for weakly conducting fluids—an experimental validation. (4th November 2016) - Wiederhold, A; Ebert, R; Weidner, M; Halbedel, B; Fröhlich, T; Resagk, C
Abstract: The Lorentz force velocimetry (LFV) is a highly feasible contactless method for measuring flow rate in a pipe or in a channel. This method has been established for liquid metal flows but also for weakly conducting electrolytes where the Lorentz force amplitudes are typically six orders smaller than the ones from liquid metal flows. Due to an increased resolution of the Lorentz force measurements which was the main focus of research in the last years, now it is possible to investigate the influence of the flow profile on the amplitude of the Lorentz force. Even if there is a semi-theoretical approach an experimental validation is still outstanding. Therefore we have tested symmetric and asymmetric flow profiles to test the LFV for weakly conducting fluids for typical industrial flows. Salt water has been used as a test electrolyte with constant values of the electrical conductivity from 0.035 to 20 S m −1 and of the flow velocity in a range of 0.5–3 m s −1 . We confirmed by extensive measurements that LFV is a suitable method for flow measurements even for different flow profiles within 5% measurement uncertainty. For a wide range of applications in research and industry the LFV should be not sensitive to various flow profiles.